2015
DOI: 10.1177/1556264615599685
|View full text |Cite
|
Sign up to set email alerts
|

Decisions by Finnish Medical Research Ethics Committees

Abstract: Review by research ethics committees (RECs) is the key in medical research regulation. Data from meeting notes and project summaries were abstracted from all projects submitted in 2002 (n = 1,004) and 2007 (n = 1,045) to the official medical RECs in Finland. Data from consecutive submissions were combined per project. When comparing RECs, logistic regression was used to adjust for application characteristics. The number of projects handled varied notably by REC. In the first handling, 85% of applications in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…This article addressed a basic descriptive question—“what are the ethical issues raised by RECs reviewing biomedical research in South Africa?” The most frequent ethical issue identified in our study was informed consent—a finding comparable with similar studies in South Africa (Clarke, 2014; Cleaton-Jones, 2010; Tsoka-Gwegweni & Wassenaar, 2014), the United Kingdom (Angell, Bryman, Ashcroft, & Dixon-Woods, 2008; Boyce, 2002), the United States (Lidz et al, 2012), Thailand (Adams et al, 2017), the Netherlands (van Lent, Rongen & Out, 2014), France (Decullier, Lhéritier, & Chapuis, 2005), Brazil (Bueno et al, 2009), Spain (Dal-Ré, Morejón & Ortega, 2004; Martín-Arrabis, Rodríguez-Lozano, & Arias-Díaz, 2012), and Finland (Hemminki, Virtanen, & Regushevskaya, 2015). A German study reported that of 1,299 queries, 53% concerned the patient information and consent document (Russ, Busta, Riedel, Zollner, & Jost, 2009).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This article addressed a basic descriptive question—“what are the ethical issues raised by RECs reviewing biomedical research in South Africa?” The most frequent ethical issue identified in our study was informed consent—a finding comparable with similar studies in South Africa (Clarke, 2014; Cleaton-Jones, 2010; Tsoka-Gwegweni & Wassenaar, 2014), the United Kingdom (Angell, Bryman, Ashcroft, & Dixon-Woods, 2008; Boyce, 2002), the United States (Lidz et al, 2012), Thailand (Adams et al, 2017), the Netherlands (van Lent, Rongen & Out, 2014), France (Decullier, Lhéritier, & Chapuis, 2005), Brazil (Bueno et al, 2009), Spain (Dal-Ré, Morejón & Ortega, 2004; Martín-Arrabis, Rodríguez-Lozano, & Arias-Díaz, 2012), and Finland (Hemminki, Virtanen, & Regushevskaya, 2015). A German study reported that of 1,299 queries, 53% concerned the patient information and consent document (Russ, Busta, Riedel, Zollner, & Jost, 2009).…”
Section: Discussionsupporting
confidence: 88%
“…A Finnish study reported scientific issues, particularly regarding methodology, to be the most frequent queries raised by RECs (Happo, Halkoaho, Lehto, & Keranen, 2016). Similarly, Hemminki et al (2015) found that scientific issues were the second most frequent REC queries in their study. Some commentators question whether RECs should review the scientific issues and study designs chosen by researchers to achieve their scientific objectives (Edwards, 2010;Humphreys, Thomas, & Martin, 2014).…”
Section: Discussionmentioning
confidence: 86%
“…The majority of the committee expectations and concerns identified in this study focused on having detailed participant information sheets, obtaining informed consent, having justified study methods and procedures and ensuring a clear and unbiased recruitment plan. These committee expectations and concerns are very similar to those identified in studies involving adults and healthy children, where the main committee concerns are related to informed consent, [31][32][33][34] confidentiality, 31,[35][36][37] scientific design 31,32,34,35,37,38 and recruitment. 31,35,38 These findings suggest that the review process is equivalent, at least in terms of the types of decisions made and concerns and expectations expressed, for applications involving seriously ill children as well as applications involving other populations.…”
Section: What This Paper Adds?mentioning
confidence: 61%
“…Analysis of REC letters to researchers enables the definition of what RECs identify as attributions in their role as gatekeepers. In most cases, authors classify REC queries according to predetermined categories on the basis of ethical guidelines, whereas other authors base their analyses on identifying problematic documents within research folders (Dal-Ré et al, 2004; Happo et al, 2017; Hemminki et al, 2015; Lukaseviciene et al, 2020; Martín-Arribas et al, 2012; Silaigwana & Wassenaar, 2019; Tersmette & Engberts, 2017). Informed consent is the most frequent topic of queries from RECs (and therefore, informed consent documents are the most common problematic documents) (Boyce, 2002; Decullier et al, 2005; Tsoka-Gwegweni & Wassenaar, 2014).…”
Section: Introductionmentioning
confidence: 99%